Anthropogenic Aerosols Delay the Emergence of GHGs‐Forced Wetting of South Asian Rainy Seasons Under a Fossil‐Fuel Intensive Pathway - Jitendra Singh; Benjamin I. Cook; Kate Marvel; Sonali McDermid; Geeta G. Persad; Bala Rajaratnam; Deepti Singh (Geophysical Research Letters, 2023)
Abstract With continued fossil‐fuel dependence, anthropogenic aerosols over South Asia are projected to increase until the mid‐21st century along with greenhouse gases (GHGs). Using the Community Earth System Model (CESM1) Large Ensemble, we quantify the influence of aerosols and GHGs on South Asian seasonal precipitation patterns over the 21st century under a very high‐emissions (RCP 8.5) trajectory. We find that increasing local aerosol concentrations could continue to suppress precipitation over South Asia in the near‐term, delaying the emergence of precipitation increases in response to GHGs by several decades in the monsoon season and a decade in the post‐monsoon season. Emergence of this wetting signal is expected in both seasons by the mid‐21st century. Our results demonstrate that the trajectory of local aerosols together with GHGs will shape near‐future precipitation patterns over South Asia. Therefore, constraining precipitation response to different trajectories of both forcers is critical for informing near‐term adaptation efforts.